University's official website design framework using human computer interaction rules - Ong , Lyn Huey (2014)
Nowadays, many universities use website as communication and promotion tools between end user and university. Various styles and principal being used by the formal university portal, and the design depend upon to the designer's decision. Users can see the different design style in university website. Thus, in order to make sure every single university official website has a standardize user interface designs, this research is carried out to overcome the various designs of formal university website. This thesis discusses on the implementation of new standard human-computer interaction rule for designing university official website. The main objective of the research is to create a new standard human-computer interaction rule which suitable to be use in designing university official website. Besides that, researcher has to determine all important elements which need to be included in one's university official website and create a university official website prototype. First of all, researcher do some preliminary studies on every existing human-computer interaction rule together with the design framework. Next, pre-stage survey forms are distributed to target respondent for the purpose of collecting user's preference and requirement. After gathering requirement stage, researchers start to analyze preliminary study result and pre-stage survey results. During design phase, story board and framework are formed according to collected result from previous stage. While in development and implementation stage, researchers create a brand new standard human-computer interaction rule, then implement the new rule in designing the prototype of university official website. Lastly, the prototype is test and evaluate by end user and its' result will be collect and analyze. As a conclusion, after completing every research process, researcher is able to propose a new standard human-computer interaction rule which suits to be used in designing university official website. In consequence, from the result collected in testing stage, it proves that the new standard human-computer interaction rule which being created and implemented to prototype design is being accepted by the end user. This is because a total of 50 respondents who include teenagers, former and present university students have taken part in the testing stage. From the post-survey result, every survey question which related to new standard human-computer interaction rules gets a total of over 80% agreement value. Therefore, from this value of percentage, it shows that new standard human-computer interaction rule is suitable to be used in designing and standardization of university official website in Malaysia.